Protocol for analysing the epidemiology of maternal mortality in Zimbabwe: A civil registration and vital statistics trend study. - Reuben Musarandega (Public Library of Science (PLoS), 2021)
Background Sub-Saharan Africa (SSA) carries the highest burden of maternal mortality, yet, the accurate maternal mortality ratios (MMR) are uncertain in most SSA countries. Measuring maternal mortality is challenging in this region, where civil registration and vital statistics (CRVS) systems are weak or non-existent. We describe a protocol designed to explore the use of CRVS to monitor maternal mortality in Zimbabwe-an SSA country. Methods In this study, we will collect deliveries and maternal death data from CRVS (government death registration records) and health facilities for 2007-2008 and 2018-2019 to compare MMRs and causes of death. We will code the causes of death using classifications in the maternal mortality version of the 10th revision to the international classification of diseases. We will compare the proportions of maternal deaths attributed to different causes between the two study periods. We will also analyse missingness and misclassification of maternal deaths in CRVS to assess the validity of their use to measure maternal mortality in Zimbabwe. Discussion This study will determine changes in MMR and causes of maternal mortality in Zimbabwe over a decade. It will show whether HIV, which was at its peak in 2007-2008, remains a significant cause of maternal deaths in Zimbabwe. The study will recommend measures to improve the quality of CRVS data for future use to monitor maternal mortality in Zimbabwe and other SSA countries of similar characteristics.